2021
DOI: 10.1186/s40001-021-00545-3
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic fracture during shoulder dislocation reduction: characteristics, management and outcomes

Abstract: Background Shoulder dislocation and the cases of iatrogenic fractures during manual reduction are becoming increasingly common. The aim of this study was to investigate the characteristics, management, and patient outcomes of iatrogenic proximal humeral fracture during the manual reduction of shoulder dislocation. Methods A retrospective and multi-center study was performed to identify all patients presenting with shoulder dislocation from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…They concluded that maintaining an optimal level of muscle relaxation reduces the risk of iatrogenic fractures. 19 The risk of an iatrogenic After closed reduction, the conservative treatment protocol consisted of immobilization of the shoulder in internal rotation for 6 weeks in an arm sling. Passive pendulum exercises were performed out of the sling during this period.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that maintaining an optimal level of muscle relaxation reduces the risk of iatrogenic fractures. 19 The risk of an iatrogenic After closed reduction, the conservative treatment protocol consisted of immobilization of the shoulder in internal rotation for 6 weeks in an arm sling. Passive pendulum exercises were performed out of the sling during this period.…”
Section: Methodsmentioning
confidence: 99%
“…Closed reduction of shoulder dislocation may be attempted successfully until 1 week of the dislocation. 4 Closed reductions of chronic and missed dislocation of 1-3 weeks duration may be attempted with success in only some cases in the young age group; 5 but the forceful closed reduction maneuvers increase risks of fracture 6 and iatrogenic damage, especially in the elderly patient. 7 , 8 Vascular damage has been reported in some instances after forceful closed reduction in the elderly age group.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle contraction was often reported to cause difficulty, pain, and even iatrogenic fracture during reduction [ 17 , 18 ]. In our study, the chair’s backrest helped prevent the patients from contracting their muscles, and none of the patients had any such complications.…”
Section: Discussionmentioning
confidence: 99%